The utility of using peak expiratory flow and forced vital capacity to predict poor expiratory cough flow in children with neuromuscular disorders - Brenda M. Morrow; Lauren Angelil; Juliet Forsyth; Ashleigh Huisamen; Erin Juries; Lieselotte Corten (AOSIS, 2019)
Background: Approximately one in every 1200 South Africans is affected by a neuromuscular disease (NMD). Weak respiratory muscles and ineffective cough contribute to the development of respiratory morbidity and mortality. Early identification of individuals at risk of respiratory complications, through peak expiratory cough flow (PCF) measurement, may improve patient outcomes through timely initiation of cough augmentation therapy. Objectives: The aim of this study was to investigate the relationship between peak expiratory flow (PEF), forced vital capacity (FVC) and PCF in South African children with neuromuscular disorders. Methods: A retrospective descriptive study of routinely collected data was conducted. Results: Forty-one participants (aged 11.5 ± 3.6 years; 75.6% male) were included. There was a strong linear correlation between PCF and PEF (R = 0.78; p= 0.0001) and between PCF and FVC (R = 0.61; p = 0.0001). There was good agreement between PCF and PEF, with intraclass correlation coefficient of 0.8 (95% confidence interval, 0.7-0.9; p < 0.0001). Peak expiratory flow < 160 L.min−1 and FVC < 1.2 L were significantly predictive of PCF < 160 L.min−1(suggestive of cough ineffectiveness), whilst PEF < 250 L.min−1 was predictive of PCF < 270 L.min−1, the level at which cough assistance is usually implemented. Conclusion: PEF and FVC may be surrogate measures of cough effectiveness in children with neuromuscular disorders. Clinical implications: PEF and FVC may be considered for clinical use as screening tools to identify patients at risk for pulmonary morbidity related to ineffective cough.